PROFIL VERTIKAL HANTARAN PANAS BAWAH PERMUKAAN MANIFESTASI PANAS BUMI DI BAGIAN BARAT GUNUNG TAMPUSU - Natalia Pandoh; Heinrich Taunaumang; Jeilen Gabriela Nusa (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Indonesia is an area that has enormous geothermal potential. In North Sulawesi itself, there are three geothermal locations, including Lahendong, which is the first geothermal field in Eastern Indonesia to produce electricity, then other locations, namely in Tompaso and Kotamobagu. Strategically, Tampusu Mount is located between Tondano Lake and Linow Lake where the two lakes are the largest types of manifestation in North Sulawesi. This manifestation occurs due to the conduction of heat transfer from subsurface rock to surface rock. This study aims to analyze the distribution of temperature at shallow depths to predict the vertical profile of the thermal conductivity of geothermal manifestations in the western part of Tampusu Mount. By using surfur 11 software, it was found that the subsurface temperature distribution at shallow depths was dominated by high temperatures ranging from 30ºC - 43ºC. The lowest temperature ranges from 20ºC - 23ºC and the vertical profile of subsurface heat conduction in the western part of Tampusu Mount is not evenly distributed in each soil layer, because the temperature data obtained varies.